Quality of life of renal transplant donors - Koirala, Sagar; Chalise, Pawan Raj; Gyawali, Prem (Journal of Society of Surgeons of Nepal, 2017)
Introduction: End stage renal disease has a high rate of mortality and morbidity. Kidney transplantation remains the best treatment option in comparison to other forms of renal replacement therapy. Live related donor renal transplantation was started at TUTH in 2008. Compared to other established centers, the outcome of transplantation was comparable. Though there is considerable evidence showing that donors are able to return to their healthy life, quality of life (QOL) assessment using standardized questionnaires has not yet been done in our centre. This study was carried out in order to compare QOL before and after donor nephrectomy. Methods: Short Form 36 version 2 (SF36v2) was used to assess the quality of life of kidney donors. Interview was conducted just before and three months after donor nephrectomy. Eight domains of quality of life score were compared using SPSS 17.0. Kolmogorov Smirnov test was used to check normal distribution of data. Mean scores before and after donation was compared with paired t test. Multivariate linear regression analysis was done to find out variables predicting poorer outcome. Results: Out of eight domains of quality of life, bodily pain, physical functioning and physical role limitation were decreased 3 months after donation. However, this did not have any impact on overall quality of life of donors. Increasing age was found to an independent predicter of poorer quality of life. However gender and donation status had no significance. Conclusion: Quality of life of renal transplant donors was not affected by donor nephrectomy. Long term follow up and quality of study is required in order to assess the changes in physical health component with time.